2015
DOI: 10.2146/ajhp150221
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic foot infection caused byRaoultella ornithinolytica

Abstract: A 68-year-old man diagnosed with a diabetic foot infection caused by R. ornithinolytica was successfully treated with amoxicillin-clavulanate and ciprofloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
0
14
1
Order By: Relevance
“…9 The patient, who had diabetes, hypertension and chronic kidney disease (CKD), improved after being treated initially with piperacillin/tazobactam then tigecycline after antibiotic susceptibility testing reported that the strain was susceptible only to ertapenem, levofloxacin, and tigecycline. 9 Another diabetic foot infection with R. ornithinolytica was reported later by Kabbara et al (2015) in a 68-year old male patient. 7 The patient's past medical history included hypertension, diabetes and CKD.…”
Section: Soft Tissue Infectionsmentioning
confidence: 96%
See 3 more Smart Citations
“…9 The patient, who had diabetes, hypertension and chronic kidney disease (CKD), improved after being treated initially with piperacillin/tazobactam then tigecycline after antibiotic susceptibility testing reported that the strain was susceptible only to ertapenem, levofloxacin, and tigecycline. 9 Another diabetic foot infection with R. ornithinolytica was reported later by Kabbara et al (2015) in a 68-year old male patient. 7 The patient's past medical history included hypertension, diabetes and CKD.…”
Section: Soft Tissue Infectionsmentioning
confidence: 96%
“…9 Another diabetic foot infection with R. ornithinolytica was reported later by Kabbara et al (2015) in a 68-year old male patient. 7 The patient's past medical history included hypertension, diabetes and CKD. 7 The pathogen was identified in cultures from the ankle wound, 7 was susceptible to amoxicillin/clavulanate, cefepime, ceftazidime, ceftriaxone, ciprofloxacin, gentamicin, imipenem/cilastatin, piperacillin/tazobactam and TMP-SMX, and resistant to cefazolin.…”
Section: Soft Tissue Infectionsmentioning
confidence: 96%
See 2 more Smart Citations
“…Also, a case report has been reported after pancreaticoduodenectomy [16] as well as in diabetic limbs [17]. It has been also isolated by human saliva and in oral microbiota of healthy patients as well as dentin of infected root canals [18].…”
Section: Discussionmentioning
confidence: 97%